Pendampingan Peningkatan Usaha Ternak Sapi Pedaging melalui Program Pengembangan Masyarakat di Desa Sumber Rejeki: - Fayyadh Fadillah; Haekal, Muhammad Haekal; Tri Budiarto; Edi Wiraguna; Muhammad Iqbal Nurulhaq; Widya Hasian Situmeang (Center for Alternative Dispute Resolution and Empowerment (CARE) IPB University, 2023)
Livestock waste is all waste left over from animal husbandry activities, whether in the form of liquid waste, solid waste, or gas. Waste basically cannot be prevented but can be processed. Waste that is not maximally utilized has an impact on the environment and can pollute water, soil and air in Sumber Rejeki Village, South Kalimantan Province. One of the leading commodities in Sumber Rejeki Village, South Kalimantan Province is broiler cattle with a population in 2023 of 250 heads. This training and mentoring aims to improve the skills of farmers, the application of modern technology in livestock management, and business development through the manufacture of innovative products such as the utilization of broiler waste into organic fertilizer and liquid organic fertilizer. There are several problems that arise such as pungent odors due to the waste produced that can affect air quality. Therefore, it is necessary to have awareness of farmers to be able to process the waste produced so that it is not only disposed of but farmers can utilize the waste to be used as additional income and can reduce pollution in the village. By increasing awareness, skills, and knowledge, farmers will be able to create and open new businesses in the livestock sector and reduce existing pollution.